Removal of Suspended Solids Using Pumice Stone in Integrated Fixed Film Activated Sludge Process (Baghdad Science Journal, 2021)
Wastewater treatment plants operators prefer to make adjustments because they are more cost effective, to use the existing tank instead of building new ones. In this case an imported materials would be  used as bio-loads to increase biomass and thus maintain efficiency as the next organic loading increases.In the present study, a local substance "pumice stone" was used as a biological carrier in the aeration tank, and the experiments were carried out in five stages: without biological carriers, filling ratio of 4%,10%,20%, and25% with pumice stone, the maximum organic loading at each stage (1.1884, 1.2144, 1.9432, 2.7768, 3.3141)g BOD /l.d respectively.Other experiments were carried out to determine the best filling ratio, the SS removal ratio was (67.57%, 69.5%,79.44%,89.61%,and 99.2%) when the filling ratio with pumice stone was (0, 4, 10, 20, and 25)%  respectively, at organic loading 2 ± 0.0528 g BOD /l.d, so the best filling ratio of pumice stone was 25% .In this case an imported materials would be  used as bio-loads to increase biomass and thus maintain efficiency as the next organic loading increases.In this research, a local substance "pumice stone" was used as a biological carrier in the aeration tank, and the experiments were carried out in five stages: without biological carriers, filling ratio of 4%,10%,20%, and25% with pumice stone, The maximum organic loading at each stage (1.1884, 1.2144, 1.9432, 2.7768, 3.3141)g BOD /l.d respectively.The SS removal ratio was when we operatio without biological carriers and with pumice stone with a filling ratio of 4% (82.86 % and 84.96 %) respectively, at organic loading 1.15 ± 0.0384 g BOD / d, the SS removal ratio when using pumice stone with a filling ratio of 4% and 10% was (80.36%, 91.59%) respectively, at organic loading 1.25 ± 0.024 g BOD /l.dThe SS removal ratio when using pumice stone with a filling ratio of 10% and 20% was (79.44%, 91.23%) respectively, at organic loading 2 ± 0.0528 g BOD /l.d ,  and The SS removal ratio when using pumice stone with a filling ratio of 20% and 25% was (80.45 %, 92.28%) respectively, at organic loading 2.85 ± 0.0624 g BOD /l.d ,which means there is  improvement in yield using pumice stone with filling ratio 4%,10%,20 and 25% by 2.1% ,11.23%,11.79% and 11.83%, respectively.